Man-animal-machine:|Exploring the posthuman life in Tess of the D’Urbervilles and Lady Chatterley’s Lover - Taşdemir, Tülay Pınar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
In this thesis, I aim to present a Deleuzean posthumanist reading of Thomas Hardy’s Tess of the D’Urbervilles and D.H. Lawrence’s Lady Chatterley’s Lover. In my research, I have mainly focused on how these two early 20th century novels disrupt the centrality of the human subject and explore the ways of alternative hybrid relationships formed through the human-animal-machine affiliations. This analysis has connected the posthumanist theory with Gilles Deleuze and Felix Guattari’s writings in order to especially focus on the concepts of “becoming-animal” and “desiring-machines,” which I present as the preliminary posthumanist gestures taking place in Hardy and Lawrence’s novels. Subsequently, my interpretation sees both authors’ works as prefigurations of a posthumanist stance, rather than a nostalgic one, as is generally accepted.
Keywords: Animals in literature.; Machine theory in literature.